Penggunaan Prinsip Kesantunan Berbahasa Podhub Deddy Courbuzier (Tinjauan Pragmatik Leech) - Ahsanurrijal Ahsanurrijal (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to describe the forms of language politeness principles used in the discourse of Deddy Corbuzier's Podhub show, based on Leech's pragmatic theory. This study employs a qualitative research approach, with data analyzed descriptively using Leech's pragmatic framework. The findings indicate that the application of politeness principles in Deddy Corbuzier's Podhub show includes the maxim of tact, the maxim of generosity, the maxim of modesty, the maxim of agreement, and the maxim of sympathy. These findings demonstrate that despite Deddy Corbuzier's direct and outspoken communication style, he manages to maintain linguistic ethics by applying various politeness maxims, particularly in delivering criticism on issues without personal attacks. The implications of this study suggest the necessity for greater attention to language use, especially concerning politeness evident in every utterance, particularly within the context of public communication on digital media